Myeloperoxidase expressing tumor associated neutrophils are associated with worse prognosis in metastatic breast cancer patients - Karin Leandersson; Dag Blomgård; Oscar Tuvesson; Lisa Rydén; Caroline Bergenfelz; Anna-Maria Larsson (Scientific Reports)
Abstract Tumor associated neutrophils (TANs) exert dual and opposing functions in tumors, acting pro-tumorigenic and anti-tumorigenic, depending on tumor progression, polarization state and subtype. Consequently, the prognostic impact of TANs in breast cancer is also contradictory. Since neutrophils are critically needed to fight infections in cancer patients, the mediators leading to tumor progression need more investigation as potential future targets. The neutrophil derived mediator myeloperoxidase (MPO) is a peroxidase with dual functions in tumors, acting both immune enhancing and suppressing. Patients with metastatic breast cancer (MBC) have aggressive tumors with a dismal prognosis and urgently need novel treatment strategies. Therefore, we here aimed to investigate the prognostic impact of TANs, MPO+ TANs and MPO+ non-neutrophils using a cohort with newly diagnosed MBC patients specifically. We show that high infiltration of MPO+ TANs and MPO+ non-neutrophils in the primary tumor (PT), was associated with clinicopathological features and worse prognosis in patients with MBC. However, only infiltration of MPO+ TANs showed independent prognostic impact in multivariable analysis adjusting for other prognostic factors in MBC. The results need to be validated in a larger cohort but suggests that MPO targeting strategies could be relevant in breast cancer patients with aggressive disease.